Action stage of Changes in Smoking Behavior in Health Students in Kupang City - Enjelita Ndoen; Petrus Romeo; Elisabeth Ina Tala Pessy (Journal of Health and Behavioral Science, 2021)
Health students are individuals who have a higher level of education and knowledge in the health field. However, around 37.3% of students in Indonesia, including health students, are smokers. Previous studies have shown student smokers' desire to quit smoking. This study describes changes in smoking behavior based on the action stage on health students in Kupang City in 2021. This type of research is qualitative with in-depth interview techniques. This study recruited nine health students who had a desire to change smoking behavior. This study found that four behavioral change processes (management contingency, helping relationships, counter conditioning, and stimulus control) play an essential role in the smoking cessation process in the action stage. Thus, the intervention needs to pay attention to the involvement of the four change processes in the action stage to encourage smokers to quit smoking altogether. Interventions also need to direct smokers to start the preparation phase for change, where intentions and commitment to action can be formed and become a foundation for smokers to initiate changes in smoking behavior.